Non–invasive vulvovaginal rejuvenation: A review - Dhillon, Jesryn; Jusuf, Nelva Karmila (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Non–invasive vulvovaginal rejuvenation is a promising option for women who want to restore the appearance and function of the vagina. Vaginal atrophy and vulvovaginal laxity are caused by several circumstances, including ageing, menopause, delivery, and others. Until now, non–invasive vulvovaginal rejuvenation has not been medically indicated, but it is estimated to be the focus of cosmetic dermatology in the future. Discussion: Non–invasive vulvovaginal rejuvenation can be divided into two methods: using energy-based devices and injectables. Carbon dioxide, Erbium:YAG laser and radiofrequency are the commonly used energy-based devices. Injectables most frequently used are hyaluronic acid and platelet–rich plasma. Some additional therapies, such as vaginal bleaching and vaginal tightening, are available to complement the available modalities. Several proposed combination treatments might be used to improve treatment outcomes. Side effects and complications reported are mild, but no consensus has approved its long–term effects. The legal aspect is not to be forgotten during the whole procedure. Conclusion: Further multicenter, double–randomized studies are needed to determine these procedures' safety and efficacy.